Vertebral artery dissection in a patient with migraine treated with calcitonin gene-related peptide monoclonal antibody: a case report and FAERS database analysis - Daiki Tokuyasu; Shungo Imai; Shih-Pin Chen; Keiko Ihara; Narumi Watanabe; Yoshikane Izawa; Jin Nakahara; Satoko Hori; Tsubasa Takizawa (BMC Neurology)
Abstract Background Migraine is associated with cervical artery dissection (CeAD). Calcitonin gene-related peptide (CGRP) is a multifunctional neuropeptide with vasodilatory effects. The use of anti-CGRP monoclonal antibodies (CGRP mAb) may affect cerebrovascular disease risk; however, no reports have associated CGRP mAb with CeAD. Case presentation and FAERS database analysis We report a case of vertebral artery dissection in a 39-year-old woman with migraine treated with galcanezumab. We searched the number of cases where cerebral and cervical artery dissection were reported as adverse effects of CGRP mAb using the FDA Adverse Event Reporting System (FAERS) database. Six and ten such cases were reported regarding galcanezumab and CGRP mAbs use, respectively. The reporting odds ratios for galcanezumab and CGRP mAbs were elevated. Conclusion Although migraine is reported to be associated with CeAD, the use of CGRP mAb might be related to CeAD and warrant further investigation.